A Take-Home Message "Fall Armyworm Management in Asia and the Pacific Region" - GC, Y D (Journal of the Plant Protection Society, 2022)
A Take-Home Message "Fall Armyworm Management in Asia and the Pacific Region" - Y.D. GC